Triple Interface Passivation Strategy‐Enabled Efficient and Stable Inverted Perovskite Solar Cells. Issue 12 (13th September 2020) - Gao, Zhi‐Wen; Wang, Yong; Ouyang, Dan; Liu, Hui; Huang, Zhanfeng; Kim, Jinwook; Choy, Wallace C. H.
Abstract: Inverted perovskite solar cells (PSCs) are still suffering low power conversion efficiency because of hole accumulation and trap‐assisted non‐radiative recombination at the interface originating from the large energy offset, interface defects, and rough contact. Here, a triple passivation of the two in‐between surfaces of the hole transport layer (HTL) and perovskite is proposed. The inorganic salt of potassium thiocyanate (KSCN) is introduced to simultaneously cross‐link NiO x, HTL, and methylammonium lead iodide (MAPbI3 ), which can significantly improve both device performances and stability. In addition to potassium passivation, the thiocyanate shows two good passivation effects on perovskite and NiO x to achieve the triple passivation. The strong NiN bonding exhibits strong polar covalent bond properties to make the electron deviate from the Ni side. Meanwhile, the strong electrostatic force between S and Pb in MAPbI3 makes the Pb atomic layer closer to perovskite to restrain the I atom. Meanwhile, the KSCN modification leads to better valence band alignment. Eventually, the KSCN meditated PSCs exhibit both high efficiency of 21.23% with open‐circuit voltage of 1.14 V and improved operational stability. The demonstration of triple interface passivation contributes to establishing promising multiple passivation strategies for improving the demanding PSC performances and stability. Abstract : The inorganic salt of potassium thiocyanate plays a triple passivation role at the interface between NiO x hole transport layer and perovskite by strong covalent band and electrostatic force. It can reduce the interface defects and promote carrier extraction and transportation, which leads to high efficiency and good stability. This provides a promising multiple passivation strategy for improving perovskite solar cells performance.